2007
DOI: 10.1016/j.micres.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a newly discovered China variety of Metarhizium anisopliae (M. anisopliae var. dcjhyium) for virulence to termites, isoenzyme, and phylogenic analysis

Abstract: The efficacy of a new virulent Metarhizium anisopliae variety (M. anisopliae var. dcjhyium, DQ288247) obtained from Odontotermes formosanus in China was evaluated against the subterranean termite, O. formosanus, in the laboratory. The new variety was compared with four other virulent M. anisopliae isolates and was found to be highly infectious and virulent against termites. M. anisopliae var. dcjhyium could cause approximately 100% mortality of termites 3 days post-inoculation in the concentration of 3x10(8) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Recently, varieties have been designated within M. anisopliae : viz., acridum , anisopliae , lepidiotum , majus , dcjhyium ; and in M. flavoviride : viz., flavoviride , pemphigum , minus , novazealandicum , and M. flavoviride Type E (Driver et al. 2000; Dong et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, varieties have been designated within M. anisopliae : viz., acridum , anisopliae , lepidiotum , majus , dcjhyium ; and in M. flavoviride : viz., flavoviride , pemphigum , minus , novazealandicum , and M. flavoviride Type E (Driver et al. 2000; Dong et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory bioassay by Chandler and Davidson [8], documented higher mortality in M. anisopliae (ARSEF 7487) than L. muscarium (ARSEF 7037) in all soil based studies.…”
mentioning
confidence: 82%
“…[3,4], Beauveria bassiana [5][6][7] and Metarhizium anisopliae [8][9][10][11] have been effectively used to control aphids, lepidopteron larvae and other pests.…”
Section: Introductionmentioning
confidence: 99%
“…Common biological control measures employ natural enemies of termites such as parasites, pathogens, or predators (Grace 1997). Recent studies have shown the detrimental effects of various entomopathogenic fungi and bacteria on termites (Neves and Alves 2000, Osbrink et al 2001b, Dong et al 2007, Maketon et al 2007). …”
Section: Biological Controlmentioning
confidence: 99%